PENGANGKATAN ANAK WARGA NEGARA INDONESIA KETURUNAN TIONGHOA DAN AKIBAT HUKUMNYA - Isti sulistyorini (LPPM Universitas Pekalongan, 2013)
According to Western law gives the notion of an adopted child, which is where her emphasis to include children who knew the other children in the family to get the status and function exactly the same with her own child or a determination by the court. In the development of community life suggests that the purpose of adoption is not only, as mentioned above, but more than that, particularly with respect to the legal consequences. Adoption as a legal act can be justified if aimed at the interests and welfare of children, which is caused due to legal inheritance rights acquired an adopted child is one of the main objectives. The purpose of this study was to determine the adoption procedure, the position adopted children related to the legal effect of adoption deed Indonesian citizens of Chinese descent. In relation to the research objectives was about, so in conducting research using normative juridical (legal normative research), which refers to the material library or secondary data. Data sources consisted of primary data sources and data source support (optional), hoping to illustrate the results of a descriptive study on issues related to the procedure and the legal effect of adoption Indonesian citizens of Chinese descent. Keywords: Adoption, procedures, legal consequences.